2020
DOI: 10.3390/cancers12071891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Hematologic, Biologic and Molecular Characteristics of Patients with Myeloproliferative Neoplasms and a Chronic Myelomonocytic Leukemia-Like Phenotype

Abstract: Patients with a myeloproliferative neoplasm (MPN) sometimes show a chronic myelomonocytic leukemia (CMML)-like phenotype but, according to the 2016 WHO classification, a documented history of an MPN excludes the diagnosis of CMML. Forty-one patients with an MPN (35 polycythemia vera (PV), 5 primary myelofibrosis, 1 essential thrombocythemia) and a CMML-like phenotype (MPN/CMML) were comprehensively characterized regarding clinical, hematologic, biologic and molecular features. The white blood cell counts in MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The percentage of patients who progressed to AML in our study was also along the lines of previous reports [ 11 , 22 , 47 , 49 ]. The risk of AML transformation depends on the transformative aggressiveness of CMML and on the competing risk of dying before transformation, usually from comorbidities or consequences of cytopenia [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of patients who progressed to AML in our study was also along the lines of previous reports [ 11 , 22 , 47 , 49 ]. The risk of AML transformation depends on the transformative aggressiveness of CMML and on the competing risk of dying before transformation, usually from comorbidities or consequences of cytopenia [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a seminal paper using mutation‐specific discrimination analysis of single‐cell‐derived colonies in 28 patients with CMML, Itzykson et al could show that the main characteristics of this disease are early clonal dominance, arising at the CD34+/CD34‐stage of hematopoiesis, and granulomonocytic differentiation skewing of multipotent and common myeloid progenitors, 10 but this phenomenon has not been correlated to other features such as phenotype and clinical outcome. Since semisolid in vitro cultures from PBMNCs of normal individuals usually contain a higher concentration of BFU‐E as compared to CFU‐GM, this test may be useful for investigating skewed differentiation toward the myelomonocytic over erythroid commitment in patients 8,9 . Due to the fact that in our center the assessment of hematopoietic colony formation in vitro has been an integral part of the diagnostic work up in patients with suspected myeloid malignancies for many years 12 and these data are part of the ABCMML, 11 we had the possibility to analyze the phenomenon of myelomonocytic skewing in a relatively large cohort of patients with CMML in this retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that analysis of myelomonocytic skewing in vitro may be useful to investigate skewed differentiation toward the myelomonocytic over erythroid commitment in patients 8,9 . Since the presence of skewing may be associated with a different phenotype, a different mutational landscape and a different prognosis in patients with myeloid malignancies this in vitro test may help to comprehensively study hematopoiesis in patients with complex disturbances of blood formation.…”
Section: Introductionmentioning
confidence: 99%
“…diseases CMML associated with mastocytosis, CMML and blastic plasmacytoid dendritic cell neoplasm, CMML associated with eosinophilia (77-79), t-CMML(85), pre CMML syndromes (oligo-monocytic CMML)(86,87), CMML with JAK-2 mutation, CMML with rearranged PDGFRA, PDGFRB, FGFR1, PCM1-JAK2, other MPN (MF, PV.) with monocytosis ("MPN with CMML-like phenotype")(88) …”
mentioning
confidence: 99%